2007
DOI: 10.1073/pnas.0609103104
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular domain–domain association/dissociation and phosphoryl transfer in the mannitol transporter of Escherichia coli are not coupled

Abstract: The Escherichia coli mannitol transporter (II Mtl ) comprises three domains connected by flexible linkers: a transmembrane domain (C) and two cytoplasmic domains (A and B). II Mtl catalyzes three successive phosphoryl-transfer reactions: one intermolecular (from histidine phosphocarrier protein to the A domain) and two intramolecular (from the A to the B domain and from the B domain to the incoming sugar bound to the C domain). A key functional requirement of II Mtl is that the A and B cytoplasmic domains be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
(70 reference statements)
3
21
0
Order By: Relevance
“…We exclude the possibility that contaminating EI and HPr in the preparation of EIC or EIN have caused the phosphorylation reaction in our study. First, EIN was not 15 N-IIA Mtl with EIC using the same buffer composition as was used to phosphorylate EIN, the spectra clearly indicated that IIA Mtl remained in the unphosphorylated state (Supporting Information Fig. 1S).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We exclude the possibility that contaminating EI and HPr in the preparation of EIC or EIN have caused the phosphorylation reaction in our study. First, EIN was not 15 N-IIA Mtl with EIC using the same buffer composition as was used to phosphorylate EIN, the spectra clearly indicated that IIA Mtl remained in the unphosphorylated state (Supporting Information Fig. 1S).…”
Section: Resultsmentioning
confidence: 99%
“…A covalent linker connecting the domains makes the association a unimolecular reaction which assures fast association kinetics defined by the size of the linker. 15 This can be a useful strategy for PTS in which rapid association and dissociation coupled with phosphotransfer reactions are important for prompt sugar uptake and phosphorylation in bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). Although binding is weak, in the context of intact IIAB Man , where the A and B domains are connected by a flexible 25-residue linker, one can calculate (11,51), based upon the expected average end-to-end distance of ϳ50 Å for the linker (52), that there would be an ϳ85% probability of the two domains interacting with one another at any given time. Man or IIB Man occurs upon binding (at the level of detection of the NMR data).…”
Section: Resultsmentioning
confidence: 99%
“…40. In the presence of catalytic amounts of EI and excess PEP, both proteins are fully phosphorylated.…”
Section: Table 2 Equilibrium Dissociation Constants (K D ) Binding Fmentioning
confidence: 99%